Data Collection for Migrant Live-In Domestic Workers: A Three-Stage Cluster Sampling Method. (May 2020) - Chung, Roger Yat-Nork; Liao, Tim F.; Fong, Eric
This article discusses an innovative method of collecting survey data on a special population, migrant live-in domestic workers, for which it is difficult to define an appropriate sampling framework. These migrant workers, however, have regular gatherings in public spaces within a certain period of time during the weekends. In this article, we present the method of collecting data on this group of domestic workers and the procedures for implementing the method. We also discuss its limitations, the difficulties encountered, as well as possible directions for improving the method in the future.